Mg2+-dependent facilitation and inactivation of L-type Ca2+ channels in guinea pig ventricular myocytes - Meimi Zhao; Rui Feng; Dongxue Shao; Shuyuan Liu; Ming Lei; Hongmei Wang; Xuefei Sun; Feng Guo; Huiyuan Hu; Masaki Kameyama; Liying Hao (Elsevier, 2015)
This study aimed to investigate the intracellular Mg2+ regulation of the L-type Ca2+ channels in guinea pig ventricular myocytes. By adopting the inside-out configuration of the patch clamp technique, single channel currents of the L-type Ca2+ channels were recorded at different intracellular Mg2+ concentrations ([Mg2+]i). At free [Mg2+]i of 0, 10−9, 10−7, 10−5, 10−3, and 10−1 M, 1.4 μM CaM + 3 mM ATP induced channel activities of 44%, 117%, 202%, 181%, 147%, and 20% of the control activity in cell-attached mode, respectively, showing a bell-shaped concentration-response relationship. Moreover, the intracellular Mg2+ modulated the Ca2+ channel gating properties, accounting for alterations in channel activities. These results imply that Mg2+ has a dual effect on the L-type Ca2+ channels: facilitation and inhibition. Lower [Mg2+]i maintains and enhances the basal activity of Ca2+ channels, whereas higher [Mg2+]i inhibits channel activity. Taken together, our data from the application of an [Mg2+]i series suggest that the dual effect of Mg2+ upon the L-type Ca2+ channels exhibits long open-time dependence.